2009
DOI: 10.1098/rspb.2009.1296
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and life-history factors influencing the evolution of maternal antibody allocation: a phylogenetic comparison

Abstract: Maternally derived yolk antibodies provide neonates with immune protection in early life at negligible cost to mothers. However, developmental effects on the neonate's future immunity are potentially costly and thus could limit yolk antibody deposition. The benefits to neonatal immunity must be balanced against costs, which may depend on neonate vulnerability to pathogens, developmental trajectories and the immunological strategies best suited to a species' pace of life. We measured yolk antibodies and life-hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Our results thus highlight that the maternal transfer of antibodies may well be a key example of an adaptive transgenerational-induced response with far-reaching implications [52,53]. The only study that investigated the relationship between the transfer of maternal antibodies and the pace of life suggested that slow-living species deposit less immunoglobulin Y (IgY) in the yolk of their eggs [12]. However, this study is based on the quantification of levels of antibodies in the egg yolk and did not consider the persistence of the transferred antibodies in the newborn, nor accounted for the level of circulating antibodies in the mother plasma at the time of egg laying.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results thus highlight that the maternal transfer of antibodies may well be a key example of an adaptive transgenerational-induced response with far-reaching implications [52,53]. The only study that investigated the relationship between the transfer of maternal antibodies and the pace of life suggested that slow-living species deposit less immunoglobulin Y (IgY) in the yolk of their eggs [12]. However, this study is based on the quantification of levels of antibodies in the egg yolk and did not consider the persistence of the transferred antibodies in the newborn, nor accounted for the level of circulating antibodies in the mother plasma at the time of egg laying.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, this receptor is also responsible for the uptake of antibodies from the egg yolk in the hatchling [60]. An increase in the expression of the FcRY or in the strength of the FcRY-IgY interaction could thus not only contribute to greater half-lives of IgY but would also help hatchlings achieve high levels of circulating IgY despite a possible lesser investment of females in egg yolk deposition of IgY in longer lived birds [12]. Evidence for the possibility of such mechanisms comes from studies of the mammalian counterpart of FcRY, the neonatal Fc receptor (FcRn), which is implicated in both the transfer of antibodies from mother to young and the recycling of IgG (see [61] for a review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly hatched ducklings depend on maternal immunoglobulin Y (IgY), which is the primary antibody in serum and the principal antibody involved in defense against systemic infections (Davison et al, 2008;Lundqvist et al, 2006). The passive immunity provided by the mother to the hatchling protects the offspring against disease agents present in the environment, and can be especially important in dense breeding populations where disease transmission may be enhanced (Addison et al, 2009;Garnier et al, 2012). Maternal IgY will form complexes with antigens to protect the duckling and alleviate pressure on the duckling's developing immune system (Addison et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, nongenetically based immune information may also influence mate choice and is the focus of the present paper. For example, the transfer of parental immune experience to offspring, socalled trans-generational immune priming (TGIP), can result in an induced offspring immune response against prevailing parasite genotypes (Sadd et al 2005;Boulinier and Staszewski 2008;Addison et al 2009;Jokela 2010;Roth et al 2010;Sepp et al 2011;Moreau et al 2012;Zhang et al 2013). Mate choice favoring individuals with immune experience may also pay off as previous parasitic experience could result in increased investment into reproduction, since the likelihood to survive and reproduce in the future is decreased (terminal investment theory: Clutton-Brock 1984;Simmons 1994;Bonneaud et al 2004).…”
Section: Introductionmentioning
confidence: 99%